2023
DOI: 10.1186/s12954-023-00754-5
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence, correlates, and access to harm reduction services among people who inject drugs living with and without HIV and their partners in Kenya

Abstract: Background In sub-Saharan Africa many people who inject drugs (PWID) are living with undiagnosed or untreated HIV and experience high levels of poverty and conditions that can contribute to worse outcomes from SARS-CoV-2 infection. Identifying the burden of SARS-CoV-2 infection in marginalized populations like PWID may contribute to controlling the pandemic. Methods This is a nested cross-sectional study within an ongoing cohort study that recruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
1
1
Order By: Relevance
“…Although the prior study found positive associations between incarceration and engagement in sex work and infection-induced SARS-CoV-2 seroprevalence, our study was underpowered to detect these associations. It is notable that our study and two prior studies did not find associations between recent substance use behaviors and infection-induced SARS-CoV-2 seroprevalence ( Doshi et al., 2023 ; Strathdee et al., 2021 ). While substance use may play a role in the pathogenesis of COVID-19 ( Ao et al., 2022 ; Hasin et al., 2022 ; Krawczyk et al., 2023 ; Wang et al., 2021 ), it may not be a salient risk factor of SARS-CoV-2 infection among people who use drugs.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Although the prior study found positive associations between incarceration and engagement in sex work and infection-induced SARS-CoV-2 seroprevalence, our study was underpowered to detect these associations. It is notable that our study and two prior studies did not find associations between recent substance use behaviors and infection-induced SARS-CoV-2 seroprevalence ( Doshi et al., 2023 ; Strathdee et al., 2021 ). While substance use may play a role in the pathogenesis of COVID-19 ( Ao et al., 2022 ; Hasin et al., 2022 ; Krawczyk et al., 2023 ; Wang et al., 2021 ), it may not be a salient risk factor of SARS-CoV-2 infection among people who use drugs.…”
Section: Discussioncontrasting
confidence: 67%
“…Prior to the introduction of the B.1.617.2 (Delta) and B.1.1.529 (Omicron) variants of SARS-CoV-2 and widespread availability of COVID-19 vaccines, a community-based study of people currently injecting drugs that was conducted between October 2020 and June 2021 in San Diego, California and Tijuana, Mexico found that the SARS-CoV-2 seroprevalence was 36%, which exceeded estimates from the general population in each city at that time ( Strathdee et al., 2021 ). In a mixed sample of PWID and their sexual or injecting partners recruited at needle and syringe service programs and methadone clinics in Kenya between April 2021 and July 2021, 31% had anti-N antibodies ( Doshi et al., 2023 ). Given that the spread of SARS-CoV-2 has been heterogeneous by population, geography, and time throughout the pandemic, these findings on infection risk may not be generalizable or transportable to other populations, settings, or points in time ( Rudolph et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%